CORRECT FORMATION OF BONES IN WOMEN OF CHILDBEARING AGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article aims to explore the mechanisms and factors influencing bone formation in women of childbearing age. It discusses the importance of bone health during this critical period and offers insights into the role of hormones, nutrition, and physical activity. The literature analysis examines existing research on bone formation, highlighting key findings and gaps in knowledge. The methods section outlines strategies for promoting optimal bone health, while the results section presents evidence-based recommendations. Finally, the discussion section delves into the implications of bone health for women of childbearing age and concludes with suggestions for future research and public health initiatives.